Projections from the oral pontine reticular nucleus to the spinal cord of the mouse - Huazheng, L.; Watson, Charles; Paxinos, G. (Elsevier, 2015)
The present study investigated projections of the mouse oral pontine reticular nucleus (PnO) to the spinal cord by (a) injecting a retrograde tracer fluoro-gold (FG) to the lumbar cord and (b) an anterograde tracer biotinylated dextran amine (BDA) to PnO. We found that PnO projects to the entire spinal cord with an ipsilateral predominance. PnO fibers mainly travel in the ipsilateral ventral funiculus in the entire cord, terminating in laminae 7–10 with a lower density of fibers and boutons in lower segments. A small number of fibers travel in the contralateral ventral funiculus in the cervical cord with a similar terminating pattern to the ipsilateral counterpart. The present study is the first demonstration of PnO fiber terminals in the mouse spinal cord. This pathway might be responsible for muscle atonia during REM sleep, but needs physiological research to confirm this.